Dynamics of Restorative Justice Implementation Towards the Entry into Force of the New Penal and Criminal Procedure Codes: A Case Study on Ordinary Theft Cases at Pangkalpinang Police Resort - Putra, Julian Piperino; Hariansah, Syafri; Dewi, Virna (SIGn Jurnal Hukum, 2025)
The national criminal law transformation towards the effective enforcement of Law Number 1 of 2023 and Law Number 20 of 2025 demands a reorientation of law enforcement practices from a retributive to a restorative paradigm. However, the current implementation of restorative justice in ordinary theft cases at the police resort level still operates within an internal regulatory framework prone to a relevance crisis due to normative gaps with the new statutory standards. This study aims to evaluate the objectivity of existing practices, analyze the clash of norms approaching the transition period, and formulate institutional policy harmonization strategies. Employing a mixed-methods legal research approach, this study integrates a doctrinal review of Police Regulation Number 8 of 2021 with empirical data from the Pangkalpinang Police Resort, triangulating in-depth interviews with investigators, victims, and offenders. The results indicate that although existing practices have met administrative compliance requirements and provided tangible recovery benefits for victims, implementation experienced statistical stagnation in certain periods due to workload and investigators’ administrative concerns. Substantively, a fundamental incompatibility was found between the rigidity of internal police rules regarding the absolute ban on recidivists and nominal loss parameters, on the one hand, and the sentencing flexibility principles in Law Number 1 of 2023, on the other hand, as well as the misalignment of internal case exposition mechanisms with the judicial scrutiny standards mandated by Law Number 20 of 2025. This study concludes that there is an urgent need for harmonization through the establishment of a specialized supervisory unit to simulate material validity testing equivalent to that of the Preliminary Examining Judge, and the integration of customary figures’ roles in penal mediation to guarantee accountability for police discretion in the new criminal justice era.